1984
DOI: 10.1149/1.2115984
|View full text |Cite
|
Sign up to set email alerts
|

Boron and Phosphorus Determination in Low Resistivity Solar‐Grade Silicon

Abstract: A technique is developed to analyze boron and phosphorus concentrations in silicon by determining net carrier concentrations from Hall‐effect measurements. The goal of the technique is to measure these impurities in purified metallurgical silicon (PMS) which is to be ultimately used for fabricating solar cells. Net carrier concentrations are measured on two wafers cut from a second‐generation Czochralski ingot pulled from PMS. Boron and phosphorus concentrations in the PMS and the ingots are calculated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Hall effect and float zone.--There are only two methods that appear to be reliable enough to provide accurate, precise analyses for boron and phosphorus at concentrations covering the range from sub-ppma to about 100 ppma. These are the float-zone, resistivity method that is traditionally used for evaluating semiconductor-grade polycrystalline silicon, and the Hall-effect technique (5).…”
Section: Boron and Phosphorusmentioning
confidence: 99%
“…Hall effect and float zone.--There are only two methods that appear to be reliable enough to provide accurate, precise analyses for boron and phosphorus at concentrations covering the range from sub-ppma to about 100 ppma. These are the float-zone, resistivity method that is traditionally used for evaluating semiconductor-grade polycrystalline silicon, and the Hall-effect technique (5).…”
Section: Boron and Phosphorusmentioning
confidence: 99%
“…Amongst other detected phases were Al-Fe-Ti-Si, Al-Ca-Fe-Si, Al-Ca-Cu-Fe-Si, Ca-Cu-Si, Fe-Si-Ti, Ca-Fe-Si; some of them are most likely non-equilibrium phases (Meteleva-Fischer et al, 2012a). Leaching using water only (Hunt et al, 1976a(Hunt et al, , 1976b would not be efficient and much more time consuming, taking into account the low solubility in water of the abovementioned impurity phases. Thus, acid leaching is addressed to impurities precipitated in inclusions, and for MG-Si with iron as a major impurity hydrofluoric acid solution is more effective.…”
Section: Leaching Of Source Mg-simentioning
confidence: 99%
“…Quantitative results, selection of leaching agents and optimum conditions of the leaching process, obtained by various authors, differed remarkably from each other. Numerous acids (nitric (Santos et al, 1990), sulphuric (Voos, 1961), hydrochloric (Santos et al, 1990;Zhang et al, 2009) and hydrofluoric (Voos, 1961;Santos et al, 1990;Ma et al, 2009)), their mixtures (Dietl, 1983;Norman et al, 1985), and even water (Santos et al, 1990;Hunt et al, 1976aHunt et al, , 1976bChu and Chu, 1983) were found in different studies as efficient leaching agents. Double-step leaching of MG-Si at elevated temperature using hydrochloric acid (16%, 5 h, 80uC) and a relatively coarse particle fraction (116 mm), followed by hydrofluoric acid (2?5%, 2 h, 80uC), removed y85% of the impurities and resulted in 99?9% pure upgraded metallurgical grade silicon (UMG-Si) (Santos et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable importance of boron as an analyte in various matrices is reected in the history of analytical chemistry by a vast spectrum of detection methods focusing on this element. Detection methods include the Hall effect, 3 spectrophotometry with various complexing agents [4][5][6][7][8] providing competitive detection limits down to the ng mL À1 range in liquids, infrared spectrometry 9 and many more. 10 Today, mainly mass spectrometric methods, sometimes in combination with isotope dilution 11 are used, since these techniques offer very high precision, low limits of determination and additional isotopic information.…”
Section: Introductionmentioning
confidence: 99%